Inside art direction interviews and case studies - Brower, Steven (London Fairchild Books, an imprint of Bloomsbury Publishing Plc, 2015)
"For many design students, the expectation is that they will one day reach the top of the ladder within a design studio or corporation and become an art director. But what does this mean and how does a design student get there? What does an art director do? How is it different from being a designer? How does one lead and inspire a team, work with freelance designers, illustrators and photographers? How do they sell this work to editors, department heads and clients? Becoming a Successful Art Director answers all these questions for design students and professionals alike. It is at once an illustrated art book, a handbook on how to be creative in this exciting work environment, and a guide to what to expect on entering the workplace. Giving practical, hands-on advice for both beginning and advanced students, It will provide a clear picture for graphic design and illustration students of how to work with art directors and the range of industries where an art director might be employed." -- Provided by publisher.
Introduction Adventures in Publication Design A Brief History of Art Direction The Life of the Art Director Advertising, Branding and Packaging Newspapers and Magazines Book Publishing Music, Film and Theatre Collaborations and Conversations Art Direction Assignments.
Includes bibliographical references (page 229) and index.
Keywords: Commercial art -- Vocational guidance; Graphic arts -- Vocational guidance